Behaviour of sintered fly ash aggregates and steel fibers on reinforced concrete slabs subjected to punching - Babu B, Ranjith; R, Thenmozhi (Revista de la Construcción. Journal of Construction, 2022)
In this study the optimum replacement percentage of sintered fly ash aggregates in M30 grade of concrete was identified based on 28 days cubical compressive strength value. The optimum replacement of Sintered Fly ash Aggregates (SFA) is 40 %. Before identifying the optimum replacement percentage, the SFAs were tested for suitability test such as crushing strength test, impact test and water absorption test. Further, the optimum 40 % SFAs in concrete is tested for punching shear on the Reinforced Concrete (RC) slabs for a dimension of 1000 mm x 1000 mm x 100 mm. In addition to know the effect of steel fibers in RC slabs subjected to punching. A hook ended steel fibers having an aspect ratio of 55, 80 and 100 is selected and varied by volume of concrete for the punching shear values on RC slabs. The RC slabs concrete contains aspect ratio of steel fibers 55 is varied for 0.25 %, 0.5 %, 0.75 % and 1 % for volume of concrete. In addition to that a constant volume of steel fiber 0.5 % is selected for the aspect ratios of 80 and 100 for the punching shear tests. The punching shear values for the RC slabs shows that partial replacement of SFAs and steel fibers in concrete enhances the punching shear strength. These experimental tested results are compared with finite element programming (ABAQUS) and international codes such as IS 456 and ACI 2011. The experimental punching shear results were higher when compared to international codes.